Payment Systems, Monetary Policy and the Role of the Central Bank - Johnson, Omotunde (International Monetary Fund, 1998)
A payment system encompasses a set of instruments and means generally acceptable in making payments; the institutional and organizational framework governing such payments, including prudential regulation; and the operating procedures and communications network used to initiate and transmit payment information from payer to payee and to settle payments. This book, by Omotunde E.G. Johnson, with Richard K. Abrams, Jean-Marc Destresse, Tony Lybek, Nicholas Roberts, and Mark Swinburne, identifies main policy and strategic issues in payment system reform, describes the structure of payment systems in selected countries, highlights areas of consensus, and suggests the direction for future policy analysis.